A 16-Channel Synchronous Sampling Power Measurement System For Wireless Health Assistance Devices - Reuter, Lukas Michael; Weigel, Robert; Fischer, Georg (IEEE International Symposium on Medical Measurements and Apllications Proceedings (MeMeA), 2012)
A multi-channel synchronous sampling hardware for power measurement applications is described. Future body-worn medical devices for ambient assisted living should allow for battery run-times of several days without any user interaction for charging. In order to achieve this very challenging goal, a first step is the characterization of the components within medical devices by their power consumption or charging power in order to create models of power consumption over time. Medical devices often include several sensors and wireless interfaces which are known to be the most power consuming. This paper describes a hardware that is used as a tool for the measurement of power consumption of specific peripherals on a medical ambient assisted living device during development. Thus a model can be derived that can help optimizing battery run-time by deciding when to use which interface for data transmission or sensor data acquisition. Furthermore, the tool can quantify the amount of energy gained from an energy harvester. By assessing power drained from battery and power harvested the battery status over time can be studied and charging intervals derived.
elib2cris::1512001600,reuter2012a
Keywords: Ambient Assisted Living (AAL); medical devices; power measurement; wireless health assistance; energy harvesting; energy consumption characterization

A compact medical platform for mobile sensor fusion and data communication - Agethen, Roman; Reuter, Lukas Michael; Lurz, Fabian; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (IEEE International Workshop on Medical Measurements and Applications (MeMeA), 2011)
elib2cris::1512001600,agethen2011

A Low-Power Embedded Communication Platform for Medical Applications - Schwarzmeier, Andre; Reuter, Lukas Michael; Mena-Carrillo, Juan; Weber, Werner; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (46th annual conference of the German Society for Biomedical Engineering, 2012)
Introduction This paper presents a scalable, flexible and energy efficient embedded communication platform for seamless data transfer of medical sensor signals from the sensor acquisition point to a medical service centre. The presented platform can be used as an assistance system for improved medical support and care of patients and lifestyle users by providing vital parameter data to the service centre for a variety of individual assistance services. Methods The presented hardware platform is comprised of two functional blocks. A sensor platform has been implemented containing a medical device controller for collection of the data of various medical sensors connected via an analog front end or by an integrated Bluetooth transceiver module. Furthermore, a communication module including an A-GPS receiver enables GSM and UMTS data and voice connections to a central infrastructure and provides positioning data of the patient current location. The software protocol stack for the sensor data transmission is kept flexible in order to allow different communication standards. Special emphasis has been put on the energy management concept to optimize the battery life time and increase patient acceptance. Results The modular hardware and software co-design allows the connection of a wide range of different medical sensors, adjusted to the patient needs and specific use case. The use of data reduction and pre-processing techniques allows a reduction of the amount of data transferred to the infrastructure. Additionally, the centralized aggregation of sensor data enables short transmission times. This, in conjunction with an application specific energy management concept, leads to an increased battery life time. Conclusion The presented platform allows the collection of vital parameters from a variety of medical sensors for personal assistance of patients and elderly people. This concept allows new possibilities in diagnosis and treatment with the goal of an increased quality of life through the extension of independent at-home living periods.
elib2cris::1512001600,schwarzmeier2012
Keywords: Medical; Platform; Energy; Budget

A mobile microcontroller platform for sensor fusion and communication - Reuter, Lukas Michael; Agethen, Roman; Lurz, Fabian; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (Embedded World Conference, 2012)
elib2cris::1512001600,reuter2012

Energy budget in mobile health assistance systems - Reuter, Lukas Michael; Weigel, Robert; Fischer, Georg; Schwarzmeier, Andre (BMT 2012, 46. DGBMT Jahrestagung, 2012)
elib2cris::1512001600,reuter2012b

Mobile und stationaere Gesundheitsassistenzsysteme - der Markt der Zukunft? - Walk, Jasmin; Eskofier, Björn; Spallek, Johannes; Reuter, Lukas Michael (Electrical and Electronic Engineering for Communication Workshop - Entwicklerforum - Fachmesse, 2011)
elib2cris::1512001600,walk2011b